SPR: Pemberdayaan Pada Komunitas Peternak Rakyat - Muladno, Muladno; Agatha, Melfa Andraini (Sodality: Jurnal Sosiologi Pedesaan, 2023)
The School for Smallholder Livestock Farming (SPR) as a participatory learning program for smallholder livestock farmers in Indonesia has three main objectives, namely (1) changing the mindset and character of livestock farmers from individual-traditional farmers to professional mutually cooperative collective livestock entrepreneurs, (2) building mutual cooperation collective businesses in livestock and other commodities, and (3) strengthening science and technology as a basis for farmers to cultivate livestock business-oriented. This research aims to investigate the changes that occur in the community of smallholder farmers after participating in the SPR-IPB program and measure the level of effectiveness of the SPR program. The research used mixed methods with quantitative and qualitative approaches. Data collection was carried out in three locations in the community of smallholder farmers. Respondents are farmers who have graduated from the SPR program and have joined the Indonesian SPR Alumni Solidarity Association (SASPRI). The research time is one full month, in December 2022. The results of this research show that the SPR program can achieve its three goals and change the actions of farmers at the community level.